Data from: Internal cranial anatomy of Early Triassic species of †Saurichthys (Actinopterygii: †Saurichthyiformes): implications for the phylogenetic placement of †saurichthyiforms ... - Argyriou, Thodoris; Giles, Sam; Friedman, Matt; Romano, Carlo; Kogan, Ilja; Sanchez-Villagra, Marcelo R. (Dryad, 2018)
Background: †Saurichthyiformes was a successful group of latest Permian-Middle Jurassic predatory actinopterygian fishes and constituted important and widely-distributed components of Triassic marine and freshwater faunas. Their systematic affinities have long been debated, with †saurichthyiforms often being aligned with chondrosteans, a group today comprising sturgeons and paddlefishes. However, their character-rich endocranial anatomy has not been investigated in detail since the first half of the 20th century. Since that time, major advances have occurred in terms of our understanding of early actinopterygian anatomy, as well as techniques for extracting morphological data from fossils. Results: We used µCT to study the internal cranial anatomy of two of the stratigraphically oldest representatives of †Saurichthys, from the Early Triassic of East Greenland and Nepal. Our work revealed numerous previously unknown characters (e.g., cryptic oticooccipital fissure; intramural diverticula of braincase; ... : Saurichthys sp. (Greenland)PLY of all segmented structures in .zip folderGreenland Saurichthys.zipSaurichthys nepalensisPLY of braincase and rostral endocast in .zip folderAcipenser brevirostrumPLY of braincase and endocast in .zip folder ...